Modified maxillary reconstruction technique for Brown's class III defects by subdividing a rhomboid shaped iliac crest into 2 subunits. Issue 8 (11th April 2018) - Ong, Hui Shan; Yu, Miao; Liu, Jian Nan; Gil, Carlos Salcedo; Wan, Kenneth; Zhang, Chen Ping; Xu, Li Qun
Abstract: Background: Men and women share a common maxillary morphology with heterogeneity in size. This indicated that our technique of reconstruction with a rhomboid‐shaped iliac crest bone flap incorporating a 30° vertical wedge osteotomy may be widely used for Brown's class III maxillectomy defect reconstruction among a population with class I skeletal profile. The reconstruction of Brown's class III maxillary defects is extremely challenging. The purpose of this study was to closely study the maxilla geometrically in order to establish a standardized maneuver, which facilitates conversion of the iliac bone flap into a natural maxilla's contours. Methods: We evaluated the geometries of 40 adult maxillas. The perimeter lengths of perinasal and infraorbital subunits were analyzed, in addition to the intersecting angle (δ) of both subunits. Sex variation was evaluated using the Student's t test. Results: In the 80 studied unilateral maxillas (40 maxillas from 18 men and 22 women), there were no significant sex differences for δ ( P = .1527). In addition, both sexes shared common morphological features, hence, in surgical reconstruction, the δ can be constantly set at 150°. Perimeter of bone segments had a greater intersubject variability (coefficient of variation [CV] of approximately 4.5‐11). From both cadaveric dissections and clinical applications, our results have shown that our standard maneuver was reproducible and reliable in reestablishing natural facial contours. Conclusion: Our standard maneuver can serve as a universal guideline, with individualized perimeter manipulations, to yield an aesthetically natural and functional outcome.